The Need to Rethink and Redefine the Position of ESP - Stojković, Nadežda (Zbornik radova Filozofskog fakulteta u Prištini, 2018)
The present volume is dedicated to a specific strand of English language teaching (ELT) – English for Specific Purposes (ESP) and its convergent and divergent linguistic branches and disciplines. ESP has been significantly present since the latter half of the previous century as a linguistic instruction response to the societal changes in the sphere of professional and scientific communication, the rising trend of their internationalization, as well as the need to spread and disseminate the influence and impact of both. It has gained significant body of high quality research based on insightful teaching practices, as ESP is primarily pragmatics oriented form of ELT, obvious in a rising number of dedicated scientific journals (this special edition also proving to that), scientific conferences, but also academic courses and various forms of trainings.Among renown linguists who influence present day understanding of ELT and ESP, Prof. Henry Widdowson claims that the importance of ESP today outscopes that of General English and is in reality the true lingua franca, as English language as a bridge language is mostly used by an adult population for the purposes of exchanging professional information. However, since its inception as an approach to teaching English, sufficient, quality reasearch having been done, its presence and relevance are yet not fully acknowledged. Given the role ESP plays in education for scientific and professional exchange on personal but also societal levels, it needs to be redefined in terms of its relevance both for linguistics and education, for it carries potential that can significantly ease and enhance the development of all levels of social life. This issue offers a carefully selected papers with topics that illuminate major aspects of the value of ESP in these aforementioned areas. It is our hope, that this carefully designed contribution will further the changes within linguistic research and educational setting to help promote and establish ESP as a needed, individual subject in ELT practitioners training.